Usage of AI-Powered Marketing to Advance SEO Strategies for Optimal Search Engine Rankings - Bharati Rathore (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2016)
For many years, search engine optimisation (SEO) has been a critical component of digital marketing. Traditional SEO tactics, on the other hand, are no longer sufficient to stay up with continuously altering search engines and client behaviours. AI has emerged as a game-changer in the SEO sector, giving marketers with new approaches and tools for optimising their websites and content for search engines. This article presents a thorough examination of the benefits, obstacles, and best practises of integrating AI with SEO. The paper also discusses the most recent AI-powered SEO tools and approaches that may assist organisations in improving their search engine ranks, increasing website traffic, and driving conversions. Overall, the purpose of this paper is to equip marketers with a road map for using AI to revolutionise their SEO tactics.